"A More Meaningful Democracy than We Ourselves Possess": Charles S. Johnson and the Education Mission to Japan, 1945–1952. Issue 4 (November 2014) - Noble, Kenneth
Abstract : "Recommendations in the report, " stated Charles S. Johnson, "have implications for our own educational system, and perhaps for our own society." Johnson, a sociologist and Fisk University's first African-American president, addressed the 1948 South Central Forum in Chicago discussing the fundamental inconsistencies existing between democracy recommended in occupied Japan's education system and the democracy practiced in America's education system. The report Johnson's speech refers to was the product of the Education Mission to Japan: a twenty-seven-member American committee selected for their expertise as educators and scholars. Charged with an advisory role to the Supreme Commander of the Allied Powers (SCAP) and the Japanese Ministry of Education (JME), the committee's primary objective extended from SCAP's overall mission: to democratize and mollify postwar Japan. Johnson, a civil rights advocate and race relations scholar, was the sole African American and only nonwhite member of this committee.